Wireless charging and monitoring system utilizing internet of things technology for electric vehicle application - A/L Kalaihrasan, Prabakaran; Zainal, Nurfarina; Ngajikin, Nor Hafizah; Sapuan, Syarfa’ Zahirah; Jubadi, Warsuzarina Mat; Lee, Hing Wah (Institute of Advanced Engineering and Science, 2025)
Internal combustion engine (ICE) vehicles are major contributors to climate change and pollution, driving the transition to electric vehicles (EVs) as a cleaner alternative. However, EVs encounter challenges with charging infrastructure, notably the need for physical cables and issues with alignment for efficient charging. To address these problems, a wireless EV charging system has been developed using internet of things (IoT) technology for real-time monitoring and control. This system incorporates ESP32 and ESP8266 microcontrollers, infrared sensors, inductive coils, an OLED display, an ESP32-CAM module, relay modules, an AC to DC converter, a TP4056 charging module, a DC voltage sensor, and lithium-ion batteries. It employs a 20-turn coil for inductive coupled wireless power transfer (WPT), enabling the full charging of two lithium-ion batteries within 60 minutes. The system can detect an EV’s presence, display battery status on an OLED screen, and provide real-time images of the vehicle’s position through the SWEVCS mobile app. Infrared sensors ensure proper and precise alignment for effective charging. This advanced wireless charging solution enhances EV charging efficiency and convenience while supporting a more sustainable energy approach.